Early Childhood Education Teachers' Perspectives on Play-Based Learning: A Survey in Yogyakarta - Ermiyati, Ermiyati; Rohmadheny, Prima Suci; Rosada, Ulfa Danni; Hastuti, Dwi (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
This study explores and analyzes the perspectives of early childhood education (ECE) teachers in Yogyakarta regarding Play-Based Learning (PBL) and evaluates the alignment of their perspectives with PBL implementation in early childhood settings. Utilizing a mixed-methods approach, data were collected through a structured questionnaire administered via Google Forms to 41 randomly selected ECE teachers, representing 20% of the target population. The survey included 26 closed-ended items on a Likert scale and four semi-open questions for additional insights. Descriptive statistical analysis using SPSS version 26 revealed a mean perspective score of 39.5854 with a standard deviation of 6.70439, categorizing 56.1% of teachers as having a medium alignment with PBL, 26.8% as high, and 17.1% as low. Thematic analysis of qualitative responses highlighted the perceived benefits of PBL for both children and teachers, including enhanced creativity, easier engagement, and improved learning environments. Despite the limited sample size and potential biases, the findings underscore the importance of continuous professional development for ECE teachers. Future research should expand the sample size and explore additional variables influencing teachers' perspectives. These insights are crucial for policymakers and educational institutions aiming to enhance early childhood education quality through effective PBL implementation.